Reflections of Battlefield Tourist Experiences Associated with Vietnam War Sites: An Analysis of Travel Blogs - Upton, A; Schänzel, Heike; Lück, M (Taylor & Francis, 2017)
The aim of this paper is to analyse online travel blogs in order to gain an understanding of the reflections held by battlefield tourists in Vietnam. A qualitative approach utilising thematic analysis was conducted on 20 travel blogs. The findings suggest that tourists can have a deeply reflective experience at sites of past warfare, which includes cognitive dissonance to the war narrative. Tourist experiences in Vietnam presented a connection to the dead (mortality mediation), and a connection to the living (local people). These outcomes led to the overall understanding of battlefield experiences in Vietnam: The meaning of life and humanity through connecting with people, and the passing of time through the writing of history.
Keywords: Dark tourism; Battlefield tourism; Vietnam War; Tourist experience; Mortality mediation; Life affirmation; Meaning of life; Interpretation